Are Evidence Standards Different for Genomic‐ vs. Clinical‐Based Precision Medicine? A Quantitative Analysis of Individualized Warfarin Therapy. Issue 5 (10th July 2017) - Dhanda, DS; Guzauskas, GF; Carlson, JJ; Basu, A; Veenstra, DL
Abstract : Evidence requirements for implementation of precision medicine (PM), whether informed by genomic or clinical data, are not well defined. Evidence requirements are driven by uncertainty and its attendant consequences; these aspects can be quantified by a novel technique in health economics: value of information analysis (VOI). We utilized VOI analysis to compare the evidence levels over time for warfarin dosing based on pharmacogenomic vs. amiodarone‐warfarin drug–drug interaction information. The primary outcome was the expected value of perfect information (EVPI), which is an estimate of the upper limit of the societal value of conducting future research. Over the past decade, the EVPI for the pharmacogenomic strategy decreased from 1, 550 to 140 vs. 1, 220 to 280 per patient for the drug‐interaction strategy. Evidence levels thus appear to be higher for pharmacogenomic‐guided vs. drug‐interaction‐guided warfarin dosing. Clinical guidelines and reimbursement policies for warfarin PM could be informed by these findings.